2001
DOI: 10.1523/jneurosci.21-08-02630.2001
|View full text |Cite
|
Sign up to set email alerts
|

GABA Transaminase Inhibition Induces Spontaneous and Enhances Depolarization-Evoked GABA Efflux via Reversal of the GABA Transporter

Abstract: The GABA transporter can reverse with depolarization, causing nonvesicular GABA release. However, this is thought to occur only under pathological conditions. Patch-clamp recordings were made from rat hippocampal neurons in primary cell cultures. Inhibition of GABA transaminase with the anticonvulsant ␥-vinyl GABA (vigabatrin; 0.05-100 M) resulted in a large leak current that was blocked by bicuculline (50 M). This leak current occurred in the absence of extracellular calcium and was blocked by the GABA transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
153
2

Year Published

2002
2002
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(168 citation statements)
references
References 57 publications
12
153
2
Order By: Relevance
“…These asymmetries produce a DS release of GABA from the SAC onto the DS ganglion cell dendrite. Recent evidence suggests that nonvesicular, carrier-mediated GABA release, which may be the primary mechanism of GABA release from SACs (26), may be sensitive to small changes in membrane potential (30).…”
Section: Discussionmentioning
confidence: 99%
“…These asymmetries produce a DS release of GABA from the SAC onto the DS ganglion cell dendrite. Recent evidence suggests that nonvesicular, carrier-mediated GABA release, which may be the primary mechanism of GABA release from SACs (26), may be sensitive to small changes in membrane potential (30).…”
Section: Discussionmentioning
confidence: 99%
“…Cell Culture, Transfection, and Differentiation-Dentate explants were cultured as previously described (26). Briefly, dentate gyrus and CA3 regions were isolated from the hippocampi of 2-to 4-day-old Sprague-Dawley rats, maintained in culture for 8 -25 days on a Matrigel substrate (1:50 dilution, Collaborative Research), and plated on glass coverslips in medium supplemented with B-27 (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
“…The homo-or heteroexchange is another well-known mechanism, whereby a transmitter could reverse the direction of the transporter dedicated to its uptake and elicit an additional release of itself or another transmitter. This phenomenon has been described and characterized for other transmitters bearing specific transport systems, such as glutamate, GABA (Schwartz, 1982;Bernath & Zigmond, 1988;Wu et al, 2001) and monoamines (Vizi et al, 1985(Vizi et al, , 1986 and has been shown to be an important mechanism during pathological conditions and in the effect of a number of drugs acting at central targets (Vizi, 2000). Nevertheless, the possibility that ATP or adenosine could utilize such kind of mechanism and interact at the level of the release process has not been directly investigated in the central nervous system.…”
Section: Introductionmentioning
confidence: 95%